Bibliometric Analysis of All Theses on Echinococcosis in Türkiye - İsmail Davarcı; Hüseyin Güdücüoğlu (Türkiye Parazitoloji Dergisi, 2025)
Objective: Türkiye is the country with the highest number of published articles on echinococcosis worldwide, it is expected that medical specialization, PhD and master’s students in Türkiye would conduct theses on this topic. These theses can provide insights for future studies. Therefore, this study aims to evaluate the medical specialization, PhD, and master’s theses related to echinococcosis conducted in Türkiye. Methods: The relevant theses were accessed individually from the “detailed search” section of the National Thesis Center webpage of the Council of Higher Education by using the search terms “Ekinokok”, “Echinococcus”, or “Hidatik” without selecting a year range. Results: A total of 202 theses (113 medical specialization theses, 42 PhD theses, and 47 master’s theses) were included in the study. When examined on a provincial basis, it was found that the highest number of theses were conducted in Ankara (n=36). At the university level, İstanbul University had the most theses. Medical specialization theses were mostly conducted in the fields of general surgery and radiology, while PhD and master’s theses were primarily conducted in the fields of parasitology and veterinary medicine. Most of the theses conducted in the internal and surgical sciences were retrospective in design, while those in the basic sciences were mainly diagnostic in nature. A moderate positive correlation was found between the number of theses and the years for medical theses (r=0.341, p=0.027), and a strong positive correlation was found for PhD theses (r=0.505, p=0.001), master’s theses (r=0.619, p=0.000), and all theses combined (r=0.761, p=0.000). Conclusion: It was observed that at least one thesis related to echinococcosis is conducted each year, with an increase in the number of PhD and master’s theses in recent years.